Genetic mutations associated with isoniazid resistance in Mycobacterium tuberculosis: a systematic review. - Marva Seifert; Donald Catanzaro; Antonino Catanzaro; Timothy C Rodwell (PLoS ONE)
Background Tuberculosis (TB) incidence and mortality are declining worldwide; however, poor detection of drug-resistant disease threatens to reverse current progress toward global TB control. Multiple, rapid molecular diagnostic tests have recently been developed to detect genetic mutations in Mycobacterium tuberculosis (Mtb) genes known to confer first-line drug resistance. Their utility, though, depends on the frequency and distribution of the resistance associated mutations in the pathogen population. Mutations associated with rifampicin resistance, one of the two first-line drugs, are well understood and appear to occur in a single gene region in >95% of phenotypically resistant isolates. Mutations associated with isoniazid, the other first-line drug, are more complex and occur in multiple Mtb genes. Objectives/methodology A systematic review of all published studies from January 2000 through August 2013 was conducted to quantify the frequency of the most common mutations associated with isoniazid resistance, to describe the frequency at which these mutations co-occur, and to identify the regional differences in the distribution of these mutations. Mutation data from 118 publications were extracted and analyzed for 11,411 Mtb isolates from 49 countries. Principal findings/conclusions Globally, 64% of all observed phenotypic isoniazid resistance was associated with the katG315 mutation. The second most frequently observed mutation, inhA-15, was reported among 19% of phenotypically resistant isolates. These two mutations, katG315 and inhA-15, combined with ten of the most commonly occurring mutations in the inhA promoter and the ahpC-oxyR intergenic region explain 84% of global phenotypic isoniazid resistance. Regional variation in the frequency of individual mutations may limit the sensitivity of molecular diagnostic tests. Well-designed systematic surveys and whole genome sequencing are needed to identify mutation frequencies in geographic regions where rapid molecular tests are currently being deployed, providing a context for interpretation of test results and the opportunity for improving the next generation of diagnostics.